Genetic Associations With Diabetic Retinopathy and Coronary Artery Disease in Emirati Patients With Type-2 Diabetes Mellitus - Azzam, Sarah K.; Osman, Wael M.; Lee, Sungmun; Khalaf, Kinda; Khandoker, Ahsan H.; Almahmeed, Wael; Jelinek, Herbert F.; Al Safar, Habiba S. (Frontiers in Endocrinology, 2019)
Aim: Type 2 Diabetes Mellitus (T2DM) is associated with both microvascular complications such as diabetic retinopathy (DR), and macrovascular complications like coronary artery disease (CAD). Genetic risk factors have a role in the development of these complications. In the present case-control study, we investigated genetic variations associated with DR and CAD in T2DM patients from the United Arab Emirates. Methods: A total of 407 Emirati patients with T2DM were recruited. Categorization of the study population was performed based on the presence or absence of DR and CAD. Seventeen Single Nucleotide Polymorphisms (SNPs), were selected for association analyses through search of publicly available databases, namely GWAS catalog, infinome genome interpretation platform and GWAS Central database. A multivariate logistic regression test was performed to evaluate the association between the 17 SNPs and DR, CAD, or both. To account for multiple testing, significance was set at p < 0.00294 using the Bonferroni correction. Results: The SNPs rs9362054 near the CEP162 gene and rs4462262 near the UBE2D1 gene were associated with DR (OR = 1.66, p = 0.001; OR = 1.37, p = 0.031; respectively), and rs12219125 near the PLXDC2 gene was associated (suggestive) with CAD (OR = 2.26, p = 0.034). Furthermore, rs9362054 near the CEP162 gene was significantly associated with both complications (OR = 2.27, p = 0.0021). The susceptibility genes for CAD (PLXDC2) and DR (UBE2D1) have a role in angiogenesis and neovascularization. Moreover, association between the ciliary gene CEP162 and DR was established in terms of retinal neural processing, confirming previous reports. Conclusions: The present study reports associations of different genetic loci with DR and CAD. We report new associations between CAD and PLXDC2, and DR with UBE2D1 using data from T2DM Emirati patients.